2021
DOI: 10.1038/s41598-021-93485-1
|View full text |Cite
|
Sign up to set email alerts
|

Mixed and nonvaccine high risk HPV types are associated with higher mortality in Black women with cervical cancer

Abstract: We studied the incidence of HPV genotypes in mostly Black women with cervical carcinoma and correlated histopathologic tumor characteristics, immune markers and clinical data with survival. Disease-free survival (DFS) and overall survival (OS) were recorded for 60 months post-diagnosis. Fifty four of the 60 (90%) patients were Black and 36 (60%) were < 55 years of age. Of the 40 patients with typeable HPV genotypes, 10 (25%) had 16/18 HPV genotypes, 30 (75%) had one of the non-16/18 HPV genotypes, and 20 (5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…CC is one of the most serious female reproductive system tumors, which is characterized by high incidence and mortality. Women of all ages are susceptible to CC, especially the middle-aged, seriously affecting their psychological health and social activities [ 12 ]. With the rapid economic and social development and the change of people's living habits, the exposure factors of CC are increasing day by day [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…CC is one of the most serious female reproductive system tumors, which is characterized by high incidence and mortality. Women of all ages are susceptible to CC, especially the middle-aged, seriously affecting their psychological health and social activities [ 12 ]. With the rapid economic and social development and the change of people's living habits, the exposure factors of CC are increasing day by day [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some of the reasons for disparities are linked to cultural, socioeconomic, and genetic factors 41 , studies adjusted for those factors revealed a potential biological bias of higher mortality in this population 42 . We have identified one comparable study by Mendoza et al 43 with a similar population cohort, including 90% of AA women. Their study showed high PD-L1-positivity in AA women with CSCC (93.3%).…”
Section: Discussionmentioning
confidence: 92%
“…Except for Hispanic patients, historically marginalised racial/ethnic groups had disproportionately lower rates of vaccination and decreased knowledge of HPV (online supplemental table 2). Additionally, these populations had lower physician recommendation for vaccination,20–22 higher prevalence of HPV infections23–32 and were less likely to undergo primary surgery as treatment for HPV-associated cancer 33–35. Although vaccination rates among Hispanic patients were relatively high, all historically marginalised racial/ethnic populations had higher rates of HPV-associated cancer36 and worse cancer-related outcomes compared with white patients 37…”
Section: Resultsmentioning
confidence: 99%